1988
DOI: 10.2307/1241495
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical Effects of Farm Policies on Optimal Leverage and the Probability of Equity Losses

Abstract: The degree to which the use of debt is increased in response to risk-reducing and income-augmenting farm policies is studied theoretically. A mean-variance model is used to determine the optimal leverage adjustment, then the effects of policies 011 the cumulative probability of earning very low rates of return on equity are examined. The evidence suggests that farm policies induce a large enough increase in financial leverage to increase the probability offarmers having negative returns to equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 10 publications
1
46
1
Order By: Relevance
“…This is not an uncommon results, and similar results can be found in the models of Collins (1985) and Featherstone, Moss, Preckel and Baker (1988). Essentially the result states that as underlying commodity price risks rise, there will be a decrease in debt in order to keep the change in total risk constant.…”
Section: IVsupporting
confidence: 75%
See 1 more Smart Citation
“…This is not an uncommon results, and similar results can be found in the models of Collins (1985) and Featherstone, Moss, Preckel and Baker (1988). Essentially the result states that as underlying commodity price risks rise, there will be a decrease in debt in order to keep the change in total risk constant.…”
Section: IVsupporting
confidence: 75%
“…On the one hand it is well known that there are agency costs associated with business risks, particularly in the pricing and access to credit and credit markets. In agriculture Collins (1985) and Featherstone, Moss, Preckel and Baker (1988) have argued that total risk is the sum of business risk plus financial risk, and financial risk is defend as the incremental increase in the variability of the return on equity due to increased debt use. From this emerges the risk-balancing hypothesis that in order to maintain constancy in total risk any increase in leverage will need to be offset by a decrease in business (operating) risk.…”
Section: IImentioning
confidence: 99%
“…Specifically, the optimal debt to assets ratio is inversely related to BR as long as the interest rate of debt does not exceed the rate of return on assets from operations and capital gains—that is δ*σROA2=αEitalicROAi<0 which is consistent with the trade‐off derived by Gabriel and Baker ()—a decline in BR would produce an increase in desired FR, everything else held constant, for a risk‐averse expected utility maximizer. Collins () and Featherstone et al () also show formally that agricultural policies that increase income, as well as reducing risk, would induce an increase in the debt to asset ratio, which, in turn, increases FR.…”
Section: Conceptual Frameworkmentioning
confidence: 98%
“…The sources of total risk facing a business are universally equated to the sum of BR (operating) and FR (e.g., Collins ; Robison and Barry ; Featherstone et al ; Harwood et al ). BR is defined as the inherent variability in the operating performance of the firm, independent of the way the firm chooses to finance its operations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Crop insurance subsidized at the federal level, and especially utilized by major field crop producers that tend to be larger than other farms, is one risk management tool that has gained in popularity in recent years. However, research has shown that due to risk-balancing tendencies on the part of a farmer, policies that decrease the variability of farm income could induce farmers to increase their risks elsewhere, such as through increased financial risk (Featherstone et al, 1988). For example, increased financial leverage could provide incentives to increased concentration of production.…”
Section: Risk Managementmentioning
confidence: 99%